The Use of an Online Learning Site (www.talkenglish.com) in Teaching Speaking for First Grade of Junior High School Students - Irma Yesi Fitri; Aryuliva Adnan (Journal of English Language Teaching, 2021)
This paper is aimed to introduce and describe how online learning by using the website www.talkenglish.com improves student’s speaking skills. Speaking is difficult to be taught because of some factors (Jaelani and Zabidi,2020) : lack of student’s interest, lack of vocabulary, hard to focus, lack of confidence, anxiety, and fear. Considering these problems, teachers need to apply a technique in the teaching and learning process. Talk English is a website that helps people to improve their English easily. This website provides theories and practice for students in English. It relates to the availability of computers and Internet connections, using websites as online learning is possible to be done. There are 3 stages in teaching: pre-teaching activity, whilst-teaching activity, and post-teaching activity. Talk English is used in whilst-teaching activities to help students with their pronunciation. In addition, this website helps students to get the correct pronunciation of English.